Bagaimana Pandemi Covid-19 Memengaruhi Political Budget Cycle: Kasus Kerugian Daerah di Indonesia - Radityazeni, Yoga (UI Scholars Hub, 2024)
This study examines how the Covid-19 pandemic affects the political budget cycle in the election political year wich participated by incumbents and identify its impact on budget losses in Indonesia. The results of the study found that the political budget cycle occurred in the regional government budget of the simultaneous local elections. The proportion of grant spending and social assistance was higher than in other years. On the other hand, the regional elections which were held during the 2020 Covid-19 Pandemic actually significantly affected the change in the proportion of budget losses to be lower compared to other years.